A review : urban heat island and its impact on building energy consumption - Maghrabi, Ammar; Mohd Farid Mohamed; Sudharshan N. Raman; Mohd Khairul Azhar Mat Sulaiman; Wardah Fatimah Mohammad Yusoff; Abuhussain, Mohammed Awad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Civilization and urbanization are the two key demands of humans in the 20th century. Over the last few decades, a considerable number of the human population have moved to urban areas. This phenomenon has led to an explosion of the population in some of the major cities around the globe, including in Saudi Arabia. Urban Heat Island (UHI) is a climatic condition in which urban settlements experience increased air temperature than their neighboring rural counterparts. The UHI is attributed to the anthropogenic modification of land surfaces, population growth, urban development, and its consequential production of waste heat, which is endangering human health and the environment as well as the quality of living. Series of factors have been responsible for UHI, including building orientation, material albedo, land use, high-rise constructions, and human activities. The present study investigates the significance of the UHI features and their relation to building energy consumption. A list of contributing factors to UHI was identified and analyzed. The study suggests that there is a positive relationship between urban greening and urban material concerning energy consumption. Thus, this is a potential study gap that needs to be addressed to analyze the impact of UHI, particularly in the context of Saudi Arabia.